Hvorfor lykke, hvorfor nu? - Ahmed, Sara (K&K - Kultur og Klasse, 2016)
The Promise of Happiness, from which this article is taken, is a provocative cultural critique of the imperative to be happy. It asks what follows when we make our desires and even our own happiness conditional on the happiness of others: “I just want you to be happy”; “I’m happy if you’re happy.” Combining philosophy and feminist cultural studies, Sara Ahmed reveals the affective and moral work performed by the “happiness duty,” the expectation that we will be made happy by taking part in that which is deemed good, and that by being happy ourselves, we will make others happy. Ahmed maintains that happiness is a promise that directs us toward certain life choices and away from others. Happiness is promised to those willing to live their lives in the right way.